2020
DOI: 10.1101/gr.262774.120
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell analysis of human embryos reveals diverse patterns of aneuploidy and mosaicism

Abstract: Less than half of human zygotes survive to birth, primarily due to aneuploidies of meiotic or mitotic origin. Mitotic errors generate chromosomal mosaicism, defined by multiple cell lineages with distinct chromosome complements. The incidence and impacts of mosaicism in human embryos remain controversial, with most previous studies based on bulk DNA assays or comparisons of multiple biopsies of few embryonic cells. Single-cell genomic data provide an opportunity to quantify mosaicism on an embryo-wide scale. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
96
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(124 citation statements)
references
References 61 publications
(95 reference statements)
11
96
0
Order By: Relevance
“…Although we did not detect any significant morphological alterations in trisomy 21 and trisomy 15 embryos, whether there are changes at the mRNA and protein levels remains to be explored. In support of this notion, previous reports have shown marked transcriptional alterations in pre-implantation aneuploid human embryos 42,45,46 . Careful analysis of trisomy 16 embryos revealed a marked hypoproliferation phenotype specific to the trophoblast.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Although we did not detect any significant morphological alterations in trisomy 21 and trisomy 15 embryos, whether there are changes at the mRNA and protein levels remains to be explored. In support of this notion, previous reports have shown marked transcriptional alterations in pre-implantation aneuploid human embryos 42,45,46 . Careful analysis of trisomy 16 embryos revealed a marked hypoproliferation phenotype specific to the trophoblast.…”
Section: Discussionsupporting
confidence: 67%
“…These results rely on inducing aneuploidy by the drug reversine, which can cause chaotic aneuploidies 26 . Interestingly, it has been reported that while rates of aneuploidy between the trophoblast and ICM are not significantly different at the blastocyst stage, aneuploid cells are enriched in the trophoblast of in vitro cultured postimplantation human embryos 42 . Moreover, mouse epiblast cells at early post-implantation stages upregulate the expression of proapoptotic genes, which leads to a lower apoptotic threshold in embryonic versus extraembryonic cells in response to DNA damage 43,44 .…”
Section: Discussionmentioning
confidence: 99%
“…45,46 A recent analysis of published single-cell RNA-seq data concluded that 80% of human embryos harbour aneuploid cells. 47 This intrinsic genetic instability of human embryos, which gives rise to a vast array of chromosomal errors, poses a major challenge to the endometrium; how to eliminate embryos of low-fitness without compromising implantation of high-quality embryos?…”
Section: Discussionmentioning
confidence: 99%
“…Human embryo single-cell RNA-seq datasets (Xue et al 2013, Yan et al 2013, Petropoulos et al 2016 are a very valuable resource and have been used by others not only to study gene signatures of cell differentiation (Blakeley et al 2015, Stirparo et al 2018, EGA (De Iaco et al 2017), embryo metabolism (Zhao et al 2019a) and expression dynamics of sex chromosomes (Zhou et al 2019a), but also to provide insight on transcriptional regulation during human preimplantation development (Grow et al 2015, Hasegawa et al 2015, Bouckenheimer et al 2016. In addition, the impact of aneuploidy on the transcriptome at single cell level has been investigated for the first time by computationally inferring the DNA copy number genome-wide from publicly available single-cell RNA-seq data (Petropoulos et al 2016, Starostik et al 2020. By doing so, similar signatures of aneuploidy were detected, which were previously described for other cell types, such as downregulation of genes involved in proliferation, metabolism and protein processing in addition to an upregulation of immune response genes (Santaguida & Amon 2015, Chunduri & Storchová 2019.…”
Section: Human Embryo Development Uncovered By Single-cell Rna-seqmentioning
confidence: 99%